2002
DOI: 10.1002/hed.10153
|View full text |Cite
|
Sign up to set email alerts
|

Merkel cell carcinoma of the head and neck: A retrospective case series

Abstract: WLE and dissection of the lymphatic drainage basin provided the best overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
85
2
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 38 publications
1
85
2
1
Order By: Relevance
“…The median follow-up was 16 to 18 months, but the literature suggests that the majority of lymph node recurrences appear within 1 year of diagnosis. 17,22,[45][46][47] In the largest published MCC meta-analysis, it was found that the median time to lymph node recurrence was 7 months, with 75% of these events occurring within 12 months of initial treatment. 9 Nevertheless, with longer follow-up, an increase in recurrence rates may be reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median follow-up was 16 to 18 months, but the literature suggests that the majority of lymph node recurrences appear within 1 year of diagnosis. 17,22,[45][46][47] In the largest published MCC meta-analysis, it was found that the median time to lymph node recurrence was 7 months, with 75% of these events occurring within 12 months of initial treatment. 9 Nevertheless, with longer follow-up, an increase in recurrence rates may be reported.…”
Section: Discussionmentioning
confidence: 99%
“…Patients present with lymph node disease in 19% to 33% 9,13,[16][17][18] of cases. Traditional recommended practice for the regional therapy for lymph node-positive disease is completion lymphadenectomy (CLND) with or without adjuvant radiotherapy.…”
mentioning
confidence: 99%
“…Slight male predominance, mean age 68 years and almost half of the tumors located in the head and neck region. 11,14 During the course of the disease 47% of the patients progressed to metastatic dissemination, local recurrence was recorded in 42% patients. These data are also consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Radical surgery is the recommended procedure to improve prediction of better survival in MCC. 13,14 Previously, cytogenetic analyses have not shown any recurrent reciprocal translocations in MCC that would generate fusion genes or lead to activation of oncogenes. Little is thus known about the chromosomal and genetic alterations in MCC.…”
mentioning
confidence: 99%
“…Mohs micrographic technique has been recommended especially in areas with high demands on aesthetics, such as localized tumors of head and neck. Brisset et al 48 however, point to the lower survival of patients treated with Mohs technique compared to patients with extensive radical excision supplemented by cervical block dissection.…”
Section: Discusionmentioning
confidence: 99%